Therapeutic Potential of Hydroxypropyl-β-Cyclodextrin-Based Extract of Medicago sativa in the Treatment of Mucopolysaccharidoses - Fumić, Barbara; Končić, Marijana Zovko; Jug, Mario (Planta Medica, 2017)
Mucopolysaccharidoses are inherited metabolic disorders resulting in the dysfunction of enzymes involved in the degradation of glycosaminoglycans, leading to severe clinical symptoms and a significantly shortened life span of patients. Flavonoids are recognized as glycosaminoglycan metabolism modulators, able to correct glycosaminoglycan cell storage. Therefore, the aim of this work was the development of an efficient and eco-friendly extraction process of phytochemicals from Medicago sativa by simultaneous use of ultrasound extraction and hydroxypropyl-β-cyclodextrin complexation, and investigation of the potential of such an extract as a glycosaminoglycan metabolism modulator. The Box-Behnken design and response surface methodology were used in order to optimize the extraction process, considering hydroxypropyl-β-cyclodextrin concentration, ultrasonic power, and extraction time as the key parameters. The dependent variables included total phenolicand total flavonoid content, DPPH radical scavenging activity, and Fe2+ chelating activity, due to the importance of oxidative stress in the pathology of mucopolysaccharidoses. The developed technology using hydroxypropyl-β-cyclodextrin led to more selective flavonoid extraction from M. sativa than obtained either by the use of water or ethanol. The lyophilization of extracts resulted in products with high radical scavenging activity, suitable for further use. The application of 20 mM hydroxypropyl-β-cyclodextrin solution, 432 W ultrasonic power, and an extraction time of 45 min resulted in an extract with both the highest total flavonoid content and the lowest radical scavenging activity IC50. This extract reduced the levels of glycosaminoglycans in skin fibroblasts of mucopolysaccharidose III patient in a dose-dependent manner. At concentrations of 3 and 6 µg/mL, the observed levels of glycosaminoglycans were reduced by 41.2 and 51.1 %, respectively, clearly demonstrating the validity of the selected approach.
Keywords: Medicago sativa; Fabaceae; hydroxypropyl-β-cyclodextrin; polyphenols; radical scavenging activity; chelating activity; glycosaminoglycans